2021
DOI: 10.3389/fcell.2020.625105
|View full text |Cite
|
Sign up to set email alerts
|

TRIM16 Promotes Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Modulating CHIP-Mediated Degradation of RUNX2

Abstract: Bone regeneration is the ultimate goal of periodontal therapies, in which osteogenic differentiation of human periodontal ligament stem cells plays a critical role. The tripartite motif (TRIM)16, an E3 ubiquitin ligase, is downregulated in periodontal tissues of patients with periodontitis, while the role of TRIM16 in the osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) is largely unknown. Firstly, we found that TRIM16 was increased throughout the osteogenic media induced different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…A study has shown that TRIM16 and Galectin-3 coregulate the osteogenic differentiation of hBMSCs [ 49 ]. Furthermore, TRIM16 reduces CHIP, which reduces CHIP-mediated RUNX2 degradation, thus promoting osteogenic differentiation of hPDLSCs [ 50 ].…”
Section: Effect Of E3 Ubiquitin Ligases In Skeletal Cell Fate and Pat...mentioning
confidence: 99%
“…A study has shown that TRIM16 and Galectin-3 coregulate the osteogenic differentiation of hBMSCs [ 49 ]. Furthermore, TRIM16 reduces CHIP, which reduces CHIP-mediated RUNX2 degradation, thus promoting osteogenic differentiation of hPDLSCs [ 50 ].…”
Section: Effect Of E3 Ubiquitin Ligases In Skeletal Cell Fate and Pat...mentioning
confidence: 99%
“…Ring finger protein 185 inhibits the WNT signaling pathway by promoting the ubiquitination and degradation of Dvl2, thus negatively regulating osteogenic differentiation (Zhou et al, 2014). Tripartite motif (TRIM) 16 was found to stabilize RUNX2 by reducing the CHIPmediated ubiquitination and degradation of K48-linked RUNX2, thereby promoting the osteogenic differentiation of human periodontal ligament stem cells (Zhao et al, 2020). TRIM21 was reported to promote the K48-linked ubiquitination of AKT, which accelerated the degradation of AKT to inhibit the osteotropic signaling pathway, thus inhibiting the osteogenic differentiation of MSCs (Xian et al, 2022).…”
Section: Other E3 Ligasesmentioning
confidence: 99%
“…After 36 hours transfection of HEK293 cells or after 14 days odontogenic differentiation of hDPSCs, total RNA was isolated using Trizol reagent (Invitrogen) and reverse transcribed into cDNA using the PrimeScript™ RT reagent Kit (Takara, China). These genes primers have been published elsewhere [43,44]. Gene expression levels were calculated using the (2 -ΔΔCT ) method.…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%